The contributions of urban parks and parks in directing towards recreational sports practices as one of the factors in reducing delinquency and drug addiction among adolescents - guemih, Mohamed; houaoura, mouloud; aouiss, ahmed (sports creativity, 2024)
This study reviews the vital role that playgrounds and parks play in directing adolescents towards recreational sports practices as an effective means of reducing delinquency and drug addiction. Adolescence is considered one of the most critical stages of life, as individuals are most vulnerable to being affected by the environmental and social factors surrounding them. The study highlights the importance of providing safe and encouraging environments, such as barns and parks, that provide adolescents with the opportunity to participate in beneficial and fun sports activities. These environments contribute to directing their energies towards positive practices and keep them away from potential dangers such as deviance and addiction. We used the descriptive approach to study a population of adolescents on a sample of 40 young adolescents They were selected randomly from the visitors of the July 5 barn in Biskra, using a questionnaire tool to collect data. The results showed that recreational sports activities play an important role in improving the psychological and physical health of adolescents, enhance their sense of belonging to society, and help develop their social skills. These activities also contribute to building values of discipline and commitment, which reduces the possibility of them engaging in deviant or addictive behaviors.